2013
DOI: 10.5137/1019-5149.jtn.8247-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrojugular arterio-venous fistula and psudo-aneurism formation due to penetrating vertebral artery injury: case report and review of the literature

Abstract: Vertebral artery injury including thrombosis, arteriovenous fistula (AVF), pseudo-aneurysm and hemorrhage may be iatrogenic or due to penetrating or blunt trauma. Although mostly asymptomatic, vertebral artery injury may also present with vertebrobasilar insufficiency findings, cephalgia, radicular pain or myelopathy due to blockade of arterial flow, arterial steal phenomenon and venous hypertension. The gold standard for diagnosis is digital subtraction angiography (DSA). Doppler ultrasonography, magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Studies have shown that posterior spine surgeries carry the highest risk of VAI [6,9]. There are several ways to prevent intraoperative VA injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that posterior spine surgeries carry the highest risk of VAI [6,9]. There are several ways to prevent intraoperative VA injury.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of vertebral artery (VA) injury as a result of after cervical spine screw fixation surgery is about 0.2% that is about 17/8213 operations annually [1]. VA injury can lead to severe blood loss, intradural or extradural hemorrhage, and the development of arteriovenous fistulae or pseudoaneurysms [2][3][4][5][6][7][8]. Furthermore, the consequences of VA injure can be fetal and even result in death because of the difficulty in controlling the pulsating hemorrhage which can cause severe hypotension resulting in cardiac arrest and finally death.…”
Section: Introductionmentioning
confidence: 99%
“…Артериовенозные соустья при ТППА в 30 % случаев протекают бессимптомно, но почти всегда диагностируются при аускультации области гематомы шеи [17]. Это говорит о том, что физикальные методы диагностики крайне важны, даже при доступности инструментальных методов исследования.…”
Section: рис 5 контрольная ангиография: а -при антеградном контрастир...unclassified
“…There are multiple devices to perform the endovascular approach and treatment of aneurysms and pseudoaneurysms, from flow diverters, coil placement, and mixed techniques for the treatment of aneurysms and pseudoaneurysms [19,21,24,[50][51][52][53][54][55][56]; in this case, a covered stent was used with successful results. Nowadays, endovascular management for vertebral artery injury is widely facilitated by advances in techniques and devices.…”
Section: Endovascular Management Of Vertebral Pseudoaneurysmmentioning
confidence: 99%